Technological regimes or "perceived" technological regimes? Evidence from the Italian wine industry. Issue 1 (9th November 2021) - Muscio, Alessandro; Nardone, Gianluca; Stasi, Antonio
Abstract : Purpose: Technological regimes define the environment in which innovative and learning activities take place in each sector of the economy. In this paper, the authors argue that technological regimes must be interpreted and elaborated by each organisation operating within a sector in order to be implemented rationally, which leads us to the concept of perceived technological regimes. Design/methodology/approach: The authors tested the relevance of firms' perceptions of different technological regimes on a sample of wine companies in Italy. The authors run a questionnaire survey and obtained 334 clean responses. Data drawn from questionnaires were analysed via econometric analysis. Findings: The authors present empirical evidence that this perception tends to vary across different wine technologies. Additionally, the authors find evidence that firms' technology adoption, absorptive capacity and external knowledge sourcing have a strong impact on their perceptions of the relevance of a given wine-making technology. Originality/value: While individual technological regimes are characterised by systematic differences in the distribution of heterogeneous firm types, previous empirical studies have not explored whether the technological environment defining a given industry is differently interpreted and elaborated by each firm operating in it.